Perancangan Sistem Informasi E-Arsip Pada CV Asli Satia Persada Berbasis Web Menggunakan Metode Prototype - Ibnu Nur Azis; Mohamad Indra; M. Khoirusofi (CV. Shofanah Media Berkah, 2023)
E-Archive Information System have become an urgent need in this digital era, where organizations and companies are increasingly relying on digital archives to store, manage and search information efficiently. The practical work report with the title Designing a Website -Based Letter Filing System Using the Prototype Method is a discussion of the details of using e-archives in managing Incoming Letters, Outgoing Letters and Disposition Letters. The aim of developing this system is to provide ease the filing of incoming letters or outgoing letters. In addition, after the author conducted research, it turned out that there were several obstacles both facilities and infrastructure faced. The research method used in making this Practical Work Report is the approach of firsthand observation, conversations, and document analysis. In this instance, the writer conducts a firsthand observation of the relevant organization, the interview method means that the author digs up data, information and information framework from the research subject, the interview is also conducted directly to the person in charge or employee at CV Asli Satia Persada, as for the literature study method at this stage the author searches for information related to the preparation of the report either in the form of information obtained from books, journals or other materials obtained from the internet. The conclusion of writing this Practical Work report is that with this letter filing system, the person in charge or company employees do not need to write down letter data manually in the agenda book and also help in searching for incoming letters, outgoing letters or disposition letters.